Brides, Mourners, Bacchae : Women's Rituals in Roman Literature - Panoussi, Vassiliki, 1967- (Book collections on Project MUSE., 2019)
Powerful female characters pervade both Greek and Latin literature, even if their presence is largely dictated by the narratives of men. Feminist approaches to the study of women in Greek literature have helped illustrate the importance of their religious and ritual roles in public life--Latin literature, however, has not been subject to similar scrutiny. In Brides, Mourners, Bacchae, Vassiliki Panoussi takes up the challenge, exploring women's place in weddings, funerals, Bacchic rites, and women-only rituals. Panoussi probes the multifaceted ways women were able to exercise influence, even power, in ancient Rome from the days of the late Republic to Flavian times. Systematically investigating both poetry and prose, Panoussi covers a wide variety of genres, from lyric poetry (Catullus), epic (Ovid, Lucan, Valerius, Statius), elegy (Propertius, Ovid), and tragedy (Seneca) to historiography (Livy) and the novel (Petronius). The first large-scale analysis of this body of evidence from a feminist perspective, the book makes a compelling case that female ritual was an important lens through which Roman authors explored the problems of women's agency, subjectivity, civic identity, and self-expression. By focusing on the fruitful intersection of gender and religion, the book elucidates not only the importance of female religious experience in Rome but also the complexity of ideological processes affecting Roman ideas about gender, sexuality, family, and society. Brides, Mourners, Bacchae will be of value to scholars of classics and ancient religions, as well as anyone interested in the study of gender in antiquity or the connection between religion and ideology.